Interactive Wordwall Media for Developing Arabic Vocabulary and Speaking Skills in Madrasah - Henny Nuryaningtyas; Wulan Indah Fatimatul Djamilah (Nurul Jadid University, 2025)
Arabic language learning in Islamic secondary schools often faces challenges related to limited vocabulary mastery and low speaking confidence. Vocabulary is a fundamental component of maharah kalam, yet it is frequently taught through rote memorization that does not support active oral use. This study aims to examine how interactive Wordwall media enhances Arabic vocabulary mastery through speaking activities. Employing a qualitative case study design, the research also involved one Arabic teacher, ten eighth-grade students, and one curriculum coordinator. Data were collected through classroom observations, semi-structured interviews, and documentation, and analyzed using data condensation, data display, and verification. The findings reveal that Wordwall enhances students’ active use of Arabic vocabulary, increases observable engagement in speaking activities, and supports students’ confidence in maharah kalam. The novelty of this study lies in its integrative approach that connects vocabulary mastery, engagement, and speaking confidence through interactive digital media. The study recommends integrating Wordwall into Arabic speaking instruction to foster communicative competence and supportive learning environments.